Injerencia de los Estados Unidos en Guatemala y Colombia : un doble discurso de control, 1980-1985 (2015)
ABSTRACT: The arrival of Ronald Reagan to the presidency of the United States in 1981, meant a change in international relations with the world and especially to Latin America and the Caribbean. The warmongering policies of containing communism and the destabilization of pro-Soviet revolutionary movements in those territories, generated a disproportionate violence and had a directly impact over the civilian population. The common denominator in Latin American countries was the violation of human rights by military regimes or of right with affinity to the US policies. US relations with Guatemala and Colombia during Ronald Reagan’s first.